Anion Conducting Polyvinyl Alcohol/Poly(acrylamide-co-diallyldimethylammonium chloride) Film Coated ZnO for Secondary Alkaline Zinc Electrodes. (3rd September 2015) - Gan, Wengang; Zhou, Debi; Zhou, Liang; Zhang, Zejie; Zhao, Jing
Abstract : Zinc electrode with polyvinyl alcohol(PVA)/poly(acrylamide-co-diallyldimethylammonium chloride) (PAADDA) film coated ZnO was prepared by a chemical cross-linking method. The PVA/PAADDA polymer film has a three-dimensional (3D) interpenetrating network structure where PVA works as polymer matrix and PAADDA as anion charge carriers. The ZnO/PVA/PAADDA composite electrode showed much better capacity stability and electrochemical activity.